Comunicação e micro discurso do consumo: lógicas de produção dos nomes de marcas publicitárias no Brasil - Romero, Maria Irene Carballido (2014)
This dissertation starts from the premise that it is through consumption that we develop relationships, that it is through objects that we give meaning to all of that things that are around us and make day-to-day life real. In order to discuss the production of the meaning of consumption by the name of the companies, we follow the same path as Carrascoza (2003) in the studies on persuasive and creative techniques of writing, titles and slogans, implicating that there are demonstratives more and more precise in the marketing speech. This way, we get to the basic speech, the naming, which names and qualifies the brand in just one word. To understand the logics of the production of this micro-message, we have to debate about the concepts that come out as crucial for the understanding of the meaning of the objects, approaching the foundations of Modernity and consumption, the role of publicity and the brands and their influence in Capitalism, through the culture industry and, at last, we describe the logics of production of this microdiscourse in four levels: Strategic, Creative, Linguistic and cool. We conducted an ethnographic research with creators of the names of Brazilian companies and submitted it to the characteristics and rules of the French Speech Analysis, by authors like Mainguenau (2004) and Charaudeau (2008). The result lead us to the develop categories and typologies resulted by the logics of production measured and applied to our corpus: the top 25 most valuable brands in Brazil in 2013. We are Strong believers that the name of a brand has a persuasive force as a speech, even if its minimalist. The production of this mini-speech brings out the universe of sign elements of communication esponsible for turning out symbols into fetishes and it takes place in the way between the production of the goods and their consumption, therefore, it is its first meaning, the baptism. This founding speech of the brand impregnates of meaning the goods that participate in communication, social relationships and the consumption culture.